CD200 and CD200R1 are differentially expressed and have differential prognostic roles in non-small cell lung cancer. (1st January 2020) - Yoshimura, Katsuhiro; Suzuki, Yuzo; Inoue, Yusuke; Tsuchiya, Kazuo; Karayama, Masato; Iwashita, Yuji; Kahyo, Tomoaki; Kawase, Akikazu; Tanahashi, Masayuki; Ogawa, Hiroshi; Inui, Naoki; Funai, Kazuhito; et al.
ABSTRACT: CD200, a member of the immunoglobulin superfamily, interacts with its receptor CD200R1 to modulate cancer immune microenvironments. Here, we explored the clinicopathological and prognostic implications of the CD200/CD200R1 axis in non-small-cell lung cancer (NSCLC) patients. We evaluated CD200/CD200R1 expression in the tumors and stroma of 632 NSCLC patients using immunohistochemistry. Associations between CD200/CD200R1 expression levels and clinicopathological data were analyzed. We also examined their expression in lung cancer cell lines. Changes in endogenous immune-related factors and cell proliferation were evaluated by CD200 and CD200R1 knockdown and CD200Fc fusion protein administration. CD200 expression was observed mainly in the tumor, and also in the stroma among a few cases, whereas CD200R1 expression was observed in both the tumor and stroma. High tumoral CD200 expression was significantly associated with female sex, never-smoking status, adenocarcinoma histology, EGFR mutation, and a low density of tumor-infiltrating lymphocytes. Meanwhile, high CD200R1 expression in the tumor and stroma was associated with ever smoking, non-adenocarcinoma histology, and increased tumor-infiltrating lymphocytes. High CD200R1 expression was associated with worse survival (log-rank, P <.001 for both tumor and stroma), whereas high CD200 expression was associated with better survival outcomes (log-rank, P <.001). The transient knockdown of CD200R1 in lung cancer cell lines impaired cell proliferation, and the in vitro modulation of CD200 and CD200R1 altered endogenous oncogenic and inflammation-related gene expression. CD200R1 expression was associated with poor prognosis, whereas CD200 expression was an independent favorable prognostic factor. Our results suggest the importance of CD200 and CD200R1 in lung cancer biology.